Attenuated lymphocyte activation leads to the development of immunotolerance in bovine fetuses persistently infected with bovine viral diarrhea virus. Issue 3 (1st June 2020) - Georges, Hanah M; Knapek, Katie J; Bielefeldt-Ohmann, Helle; Van Campen, Hana; Hansen, Thomas R
Abstract: Bovine viral diarrhea virus continues to cost the cattle industry millions of dollars each year despite control measures. The primary reservoirs for bovine viral diarrhea virus are persistently infected animals, which are infected in utero and shed the virus throughout their lifetime. The difficulty in controlling the virus stems from a limited understanding of transplacental transmission and fetal development of immunotolerance. In this study, pregnant bovine viral diarrhea virus naïve heifers were inoculated with bovine viral diarrhea virus on day 75 of gestation and fetal spleens were collected on gestational days 82, 97, 190, and 245. Microarray analysis on splenic RNA from days 82 and 97 revealed an increase in signaling for the innate immune system and antigen presentation to T cells in day 97 persistently infected fetuses compared to controls. Reverse transcription quantitative polymerase chain reaction on select targets validated the microarray revealing a downregulation of type I interferons and lymphocyte markers in day 190 persistently infected fetuses compared to controls. Protein was visualized using western blot and tissue sections were analyzed with hematoxylin and eosin staining and immunohistochemistry. Data collected indicate that fetal immunotolerance to bovine viral diarrhea virus developed between days 97 and 190, with mass attenuation of the immune system on day 190 of gestation. Furthermore, lymphocyte transcripts were initially unchanged then downregulated, suggesting that immunotolerance to the virus stems from a blockage in lymphocyte activation and hence an inability to clear the virus. The identification of lymphocyte derived immunotolerance will aid in the development of preventative and viral control measures to implement before or during pregnancy. Abstract : Lymphocyte attenuation contributes to the establishment of immunotolerance in bovine viral diarrhea virus persistently infected fetuses. Importance Bovine viral diarrhea virus is an infectious RNA virus, which is a major cause of production losses in cattle due to its contribution to bovine respiratory disease in feedlot animals and reproductive losses in cow-calf (breeding) herds. Persistently infected, immunotolerant animals are the main source of bovine viral diarrhea virus infections in cattle. The generation of persistently infected animals by vertical transmission of bovine viral diarrhea virus during early pregnancy has been known for over 50 years; however, the mechanisms responsible for the immunotolerance to and persistence of bovine viral diarrhea virus in persistently infected animals have not been elucidated [1 –3 ]. This in vivo study provides not only a unique perspective on the development of immunotolerance to bovine viral diarrhea virus in persistently infected fetuses, but contributes to our understanding the development of the bovine fetal immune system.